Coding Bootcamps for Female Digital Employment : Evidence from a Randomized Control Trial in Argentina and Colombia - Aramburu, Julian (World Bank, Washington, DC, 2021)
The increase in female labor force participation is among the most salient economic and social transformations in the world over the last fifty years, and Latin America is no exception. In this regard, the gender gap in educational attainment has not only narrowed, but it has reversed itself in most countries of the region. Despite this, two important gaps remain. First, wages of female workers are, on average, thirty percent lower than those of males. Second, a high degree of occupational and educational segregation remains, with men and women being concentrated in different fields of occupations and study. This study pilots a comprehensive female-targeted computer programming training (bootcamp) in Buenos Aires, Argentina and Bogotá, Colombia. Bootcamps have become a policy instrument to tackle the following two objectives. First, they provide training on coding skills at a time when the rapid spread of new digital technologies is increasing demand for such skills. Second, when training on coding skills is specifically targeted toward women, it reduces the gender gap in terms of access to effective training on coding skills.